Comparison of immune responses to Brucella melitensis Rev.1 conjunctival or subcutaneous vaccinations in sexually immature endangered scimitar-horned oryx (Oryx dammah) - Lignereux, Louis; Pesci, Maria Elena; Saegerman, Claude (Veterinaria Italiana, 2024)
A single dose of 1-2 x 109 CFU of the Brucella melitensis Rev.1 vaccine strain was administered subcutaneously or conjunctivally to two groups of ten sexually immature scimitar-horned oryx (SHO). A third group of ten served as unvaccinated controls. These groups were housed together and bred, producing offspring. No clinical signs appeared during the week following administration. The rose Bengal test (RBT), a lateral flow assay (LFA), and the brucellin skin test (BST) were conducted before and during the experiment to assess humoral and cellular immune responses. These responses were rapid and strong. The cellular response was durable and similar in both groups, with 80% of vaccinated SHO still positive 184 weeks post-vaccination (PV). The conjunctival route resulted in a shorter serological response, with all animals RBT seronegative at 12 weeks PV, compared to 57% still positive at 74 weeks PV with the subcutaneous route. LFA positivity remained high in both groups until 30 weeks PV, then decreased faster in the conjunctival group. All SHO returned to LFA negativity by 74 weeks PV. No reactions to RBT and BST were observed in the control group or offspring. These findings offer a strategic approach for managing brucellosis outbreaks in captive SHO.